The Revisited BPT Diagram From The Self-Consistent Analysis - Privatus, P.; Pappalardo, C.; Rao, P. V. K.; Mazengo, D. T. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Galaxies' spectral energy distribution has been explored through the use of spectral synthesis codes, and these techniques have been essential in identifying many aspects of the current galaxy evolution model. Most of the spectral synthesis codes that have been developed so far are solely stellar and assume a negligible nebular contribution to the overall continuum. FADO (Fitting Analysis using Differential Evolution Optimisation) is the first spectral synthesis code to fit selfconsistently stellar and nebular components. Diagnostic diagrams are powerful tools for classifying galaxies based on the emission line ratio of collisionally excited lines such as [OIII] λ 5007 , [NII] λ 6584 , [SII] λ 6716 , 6731, [OI] λ 6300 , and the Balmer recombination lines such as Hα, Hβ. This paper explores the impact of including nebular components on diagnostic diagrams. We investigated the results of the application of FADO to the Sloan Digital Sky Survey Data Release 8 using the data analysed by MPA-JHU, the Max Planck Institute for Astrophysics, and Johns Hopkins University. We found that in all diagnostic diagrams, the fluxes for FADO are higher than those for MPA-JHU; the difference is significant compared to the error in the flux measurement. FADO overestimates the flux ratio of all three diagnostic diagrams over MPA-JHU, but the overestimation is comparable with the line flux ratio errors. The results indicate that the inclusion of a nebular continuum is very important when fitting the spectral energy distribution as it increases the fluxes of all galaxies. However, there is a mild impact from the inclusion of nebular component analysis in the diagnostic diagrams used to classify the ionisation state of galaxies' interstellar medium. Спектральное распределение энергии галактик было исследовано С использованием кодов спектрального синтеза, которые важны для выявления многих аспектов современных моделей эволюции галактик. Большинство кодов спектрального синтеза, разработанных до сих пор, в основном учитывают звездную компоненту и предполагают незначительный небулярный вклад в общий континуум. FADO (Fitting Analysis using Differential Evolution Optimisation) - первый код спектрального синтеза, который Самосогласованно учитывает обе компоненты. Диагностические диаграммы являются Мощным инструментом для классификации галактик на основе отношений Ударно возбуждаемых эмиссионных линий, таких как [OIII]λ 5007, [NII] λ 6584,[SII] λ 6716, 6731, [OI] λ 6300, а также рекомбинационных линий Бальмера,таких как Hα, Hβ. В данной статье исследуется влияние небулярного компонента на диагностические диаграммы. Приведены результаты применения FADO к данным Sloan Digital Sky Survey Data Release 8, в сравнении с данными, проанализированными MPA-JHU (Max Planck Institute for Astrophysics и Johns Hopkins University). Обнаружено, что на всех Диагностических диаграммах потоки для FADO выше, чем для MPA-JHU; разница Значительна по сравнению с ошибкой измерения потока. FADO переоценивает отношение потоков во всех трех диагностических диаграммах по сравнению с MPA-JHU, но переоценка сопоставима с ошибками измерения потоков линий. Результаты указывают на то, что включение небулярного континуума является важным при подгонке спектрального распределения энергии, поскольку это увеличивает потоки всех галактик. Однако включение анализа небулярного компонента оказывает незначительное влияние на диагностические диаграммы, используемые для для классификации ионизационного состояния межзвездной среды галактик.
Keywords: Astrophysics